Social Transformation and Managerial Strategies in Fire Management: A Comparative Study in Disaster Prone Areas - Supriatna, Agus; Duwila, Iwan; Sianipar, Godlif; Hidayat, Muhamad (PT. Anagata Sembagi Education, 2025)
Fire risks in disaster-prone areas are increasing due to climate change and anthropogenic activities, such as illegal land clearing and weak law enforcement, especially in Indonesia, Brazil, and Australia. This study uses a qualitative approach with literature review methods and thematic content analysis to explore the dynamics of social transformation and managerial strategies in fire management through a comparative cross-case study. Social transformation is driven by citizen participation and local actors integrating local knowledge with modern technology, such as the Masyarakat Peduli Api program in Indonesia that reduced fires by 40% and